Psychology and Constructivism in International Relations : An Ideational Alliance - Kowert, Paul, 1964-; Shannon, Vaughn P. (Book collections on Project MUSE., 2012)
Constructivist IR scholars study the ways in which international norms, culture, and identities-all intersubjective phenomena-inform foreign policy and affect the reaction to and outcomes of international events. Political psychologists similarly investigate divergent national self-conceptions as well as the individual cognitive and emotional propensities that shape ideology and policy. Given their mutual interest in human subjectivity and identity politics, a dialogue and synthesis between constructivism and political psychology is long overdue. The contributors to this volume discuss both theoretical and empirical issues of complementarity and critique, with an emphasis on the potential for integrating the viewpoints within a progressive ideational paradigm. Moreover, they make a self-conscious effort to interrogate, rather than gloss over, their differences in the hope that such disagreements will prove particularly rich sources of analytical and empirical insight.